Dimensiones latentes de la diferenciación del espacio social en una metrópolis latinoaniericana. El caso del Gran Santiago - Ortiz Veliz, Jorge; Schiappacasse Cambiaso, Paulina (Geographicalia, 2017)
In the light of a set of socioeconomical, demographia, population spatial mobility and building characteristics variables, the latent dimensions of the social space of the national capital are analysed and related with the structures linked to the social models of spatial diferentation proposed for cities of metropolitan character in Latinoamerica.